Understanding Middle Atmospheric Composition Variability from the Solar Occultation for Ice Experiment Instrument and Other Datasets - Das, Saswati (Virginia Tech, 2022)
This dissertation comprises multiple studies surrounding the middle atmosphere's chemistry, composition, and dynamics. The middle atmosphere refers to the region from ~ 10 km to ~ 100 km and consists of the Stratosphere, Mesosphere, and Lower Thermosphere. The Stratosphere, Mesosphere, and Thermosphere are bounded by pauses where the strongest changes in chemical composition, movement, density, and thermal behavior take place. While several studies in the past have investigated the chemical composition of the middle atmosphere and quantified the distribution of various species from the stratosphere to the lower thermosphere, seasonal variations and redistribution of species resulting from transport events make it important to continuously monitor the middle atmosphere. Dynamic events such as Sudden Stratospheric Warmings (SSW) impact the temperature gradient and the zonal mean wind pattern in the stratopause. Descent events triggered by SSWs result in enhanced transport of species from the lower thermosphere to the stratosphere. Temperature increments during SSWs have an important impact on Polar Stratospheric Clouds (PSCs), resulting in Antarctic ozone enhancement and a smaller ozone hole. The middle atmosphere is, thus, home to a diverse range of dynamics and chemistry, making it a critical subject that warrants attention from the science community. The continuous monitoring of the middle atmosphere is important to this end. Several satellite missions in the past have been dedicated to monitoring the middle atmosphere and collecting data for decades. However, continual revisions and revaluations of measurement approaches and the introduction of novel space instruments are necessary to compensate for the limitations associated with existing missions, expand the extant specimen database, and improve phenomenon-centric observations. The Solar Occultation for Ice Experiment (SOFIE) is one of the two instruments on the Aeronomy of Ice in the Mesosphere (AIM) spacecraft. The studies presented in this dissertation ...